Development of the SERIBU (Sex Education, Friendly and Interactive) Application as a Guidance Service Media for Preventive Efforts from Sexual Abuse - Kurniawati, Devi Ayu; Mulyawan, Galuh; Sunarti, Titi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Sexual violence against children is a global problem that affects millions of children every year. This violence often involves abuse of power by the perpetrator to force the victim to carry out unwanted actions. Seeing these conditions, sex education is an important effort to teach children how to protect themselves. Guidance and counseling (BK) services can provide psychological and emotional support to children who may have experienced violence or sexual abuse, and help them understand and manage the impact. The guidance and counseling service process requires BK teachers to use media that is easy to understand so that the material can be conveyed clearly to children. It is hoped that the development of application-based interactive educational media can facilitate children's understanding and increase their interest in learning by presenting information about sexual education through text, animated videos and interesting quizzes to test their understanding of the material presented